EFISIENSI FAKTOR-FAKTOR PRODUKSI GARAM RAKYAT - Dafid Amami; Ihsannudin Ihsannudin (Trunojoyo University of Madura, 2016)
This research mainly aims to analyze the eligibility of the salt business level, the efficiency techniques level, and the economic efficiency from salt folk production factors. Methods of analysis used are eligibility business method with R/C ratio and analysis of production efficiency with the function of Stochastic Frontier Cobb-Douglas production with frontier program 4.1c and Return to scale test. The result shows that the salt folk business stand on good position or in other word. However, that production factor of salt folk does not efficiencies yet until need to add some input in order to reach whole of efficiency.